Enzyme Supplementation to Diets Containing Wheat Distillers’ Dried Grains with Solubles (DDGS) When Fed to Laying Hens - Isobel M. Whiting; Stephen P. Rose; Ahmed M. Amerah; Vasil R. Pirgozliev (Poultry)
A study was conducted using 144 Hy-Line Brown laying hens (22 weeks old) to assess the impact of exogenous enzymes on energy utilisation and ileal nutrient digestibility in diets containing 300 g/kg wheat distillers’ dried grains with solubles (DDGS). A basal diet was prepared and divided into eight treatments: a control (C) and diets supplemented with 2000 units/kg xylanase (XYL), 500 units/kg phytase (PHY), and 4000 units/kg protease (PRO), individually and in combination. The diets were fed for nine days to six coops, each housing three birds. Feed intake, weight gain, and feed conversion ratio were recorded. The feed and excreta were analysed for gross energy, and the apparent metabolisable energy (AME) was calculated. On the final day, the birds were euthanised, and ileal digesta were collected, freeze-dried, and analysed for the digestibility coefficients of dry matter (DM), nitrogen, fat, and neutral detergent fibres (NDFs). XYL supplementation improved (p = 0.035) dietary AME but did not affect (p > 0.05) DM, nitrogen, fat, or NDF digestibility. No significant effects (p > 0.05) were observed for PHY or PRO, and no interactions (p > 0.05) were found between enzyme combinations. Substrates in experimental diets involving various enzyme combinations should be given careful consideration.